PENGARUH CAPITAL ADEQUANCY RATIO (CAR), RETURN ON ASSET (ROA), DANA PIHAK KETIGA TERHADAP JUMLAH KREDIT TERSALURKAN PADA LPD DI KABUPATEN BADUNG TAHUN 2021 - I Ketut Yudana Adi (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to determine: 1) the effect of capital adequacy ratio on the amount of disbursed loans, 2) the effect of return on assets on the amount of disbursed loans, 3). Effect of Third Party Funds on Total Disbursed Loans, 4), Capital Adequacy Ratio, Return on Assets, Third Party Funds on Total Disbursed Loans. This research was conducted on LPLPD in Badung Regency in 2021 with a total population of 122 LPD. The sampling technique in this study used the purposive sampling method, so that the research sample used was 84 LPD. The analytical technique used in this research is multiple linear regression analysis. The results of this study are 1) Capital Adequacy Ratio has a negative and insignificant effect on the Amount of Disbursed Loans, 2) Return on Assets has a negative and significant effect on the Amount of Disbursed Loans, 3) Third Party Funds have a positive and significant effect on the Amount of Disbursed Loans 4) CAR , ROA, Third party funds simultaneously have a significant effect on the amount of credit disbursed